Comparison of self-reported physical activity levels and quality of life between individuals with dysvascular and non-dysvascular below-knee amputation: A cross-sectional study. Issue 2 (April 2019) - Jayakaran, Prasath; Perry, Meredith; Hale, Leigh
Abstract: Background: Decreased physical ability of individuals with a dysvascular amputation when compared with non-dysvascular counterpart may impact on their ability to participate in regular physical activity and concomitant quality of life. Objective: To compare physical activity, quality of life (QoL), and perceptions towards exercise between individuals with dysvascular and individuals with non-dysvascular amputation. Methods: A random sample of individuals identified from the New Zealand Artificial Limb Service database, aged 18 years and over, with a unilateral below-knee amputation due to a dysvascular condition (n = 61) and trauma (n = 116) completed the self-reported survey. Main constructs measured were: self-reported physical activity levels (MET-hours/day); quality of life (EuroQoL); perceptions towards exercise (Exercise Barriers and Benefits Scale [EBBS]); mobility capability (Locomotor Capability Index [LCI]) and a customized screening questionnaire. Results: Significant differences (p ≤ 0.05) were observed between dysvascular and non-dysvascular groups for total MET-hours/day [13.2 ± 12.7; 27.0 ± 23.2], LCI [36.3 ± 17.7; 49.9 ± 13.7], EuroQoL [72.1 ± 21.7; 80.9 ± 19.3] and EBBS [78.5 ± 10.3; 85.0 ± 14.3]. Cause of amputation, age, experience with the prosthesis, presence of co-morbidities and LCI were significant (p ≤ 0.008) correlates (simple linear regression) of MET-hours/day. Age was the only significant correlate in multivariable model with 0.43 MET-hours/day [F (5, 161) = 9.28; p < 0.001], for each 1-year increase in age. Conclusion: Physical activity levels and quality of life of individuals with dysvascular amputation were lower when compared with non-dysvascular amputation. Person-centred behavioural interventions to increase physical activity levels are needed to decrease the risk for developing long-term co-morbidities and to lessen the effects of co-morbidities already present in this population.